Engineered ribosomes with tethered subunits for expanding biological function - Erik D. Carlson (Nature Portfolio, 2019)
Ribo-T is a tethered ribosome complex capable of orthogonal ribosome-mRNA functionality, but has low activity. Here the authors evolve new tether designs that support faster growth and increased protein expression.